Pengimplementasian Metode Takakura Sebagai Bentuk Kerjasama Sister City Surabaya-Kitakyushu - Puput Oktariani; Oktavia Widya Kumalasari; Dyah Estu Kurniawati (Jayapangus Press, 2022)
Surabaya city experienced problems related to waste management, action city officials have not adequately address the problems of garbage generated because the outcome is not maximized. Therefore, Surabaya formed a Sister City partnership with the City of Kitakyushu in Japan to give birth to an implementation of the method proposed by Koji Takakura is THC (Takakura Home Composting). This study aims to describe the implementation of Takakura method as a result of the cooperation of Sister City Surabaya with Kitakyushu City. This research uses a qualitative descrptive research method by using documentation study to systematically study the implementation of Sister City Surabaya and Kitakyushu on waste management. The result is cooperation of Sister City Surabaya and Kitakyushu City a practice that focuses on waste management with one implementation, namely the application of Takakura method in Rungkut Lor, Surabaya. Takakura method be an alternative way for waste management using compost fermentation process. Implementation of this Takakura method succeeded in making the citizens of Surabaya, especially in the area of Rungkut Lor reduce excessive waste production, but it is also a positive impact on the economy to society. The conclusion is practice of paradiplomacy through Sister City partnership is able to create a new innovation to resolve the problem in an area in the field of environment, especially regarding waste management by using the Takakura method.